HARGA DAN KINERJA EMAS: PERAN INTERMEDIASI BANK - Sari, Novi Primita; Sangadah, Dhurotus (Jurnal Ilmu Ekonomi, Manajemen dan Bisnis, 2024)
Abstract.   The main activities carried out by banks aim to increase equitable distribution of economic growth and maintain national stability towards increasing prosperity. Strict regulations in the banking industry require the banking industry to improve its performance, including in the aspect of achieving profits. Achieving this profit can be improved by analyzing the factors that shape profilability. The aim of the research is to find out how the role of the amount of deposits and credit mediates the influence of gold prices on return on assets. The results of this research show that individual testing to determine the determinants of savings shows that prices have a positive and significant influence while the determinants of credit, savings have a significant positive influence. Factors forming return on assets, savings and credit, have a significant positive influence on return on assets, while the price of gold has a significant negative influence. In the analysis test, the savings channel variable was able to mediate (parcel mediation) the effect of gold prices on return on assets as well as credit also showed its ability to mediate (parcel mediation) the effect of savings on return on assets. However, if you look at the VAF value, the credit variable has a better level of mediation compared to savings, so that for state-owned banks to increase return on assets it will be easier if they channel savings in the form of credit   Keywords: Gold Prices; Bank; SEM; ROA; Credit.   Abstrak.   Kegiatan utama yang dilakukan bank bertujuan untuk meningkatkan pemerataan pertumbuhan ekonomi dan menjaga stabilitas nasional menuju peningkatan kesejahteraan.. Peraturan yang ketat di Industri Perbankan mengharuskan industri perbankan untuk meningkatkan kinerjanya, termasuk dalam aspek pencapaian keuntungan. Pencapaian keuntungan ini dapat ditingkatkan dengan menganalisis bagaimana faktor-faktor yang membentuk profilitabilitas. Tujuan penelitian adalah untuk mengetahui bagaimana peran jumlah deposito dan kredit memediasi pengaruh harga emas terhadap return on aset. Hasil penelitian ini menunjukkan bahwa pengujian individual untuk mengetahui determinan simpanan menunjukkan bahwa harga mempunyai pengaruh positif dan signifikan sedangkan determinan kredit, simpanan mempunyai pengaruh positif signifikan. Faktor pembentuk return on asset simpanan dan kredit mempunyai pengaruh positif signifikan terhadap return on assets sedangkan harga emas mempunyai pengaruh negatif signifikan. Dalam uji analisis, variabel jalur simpanan mampu memediasi (parcel mediation) pengaruh harga emas terhadap return on aset begitu pula dengan kredit juga menunjukkan kemampuannya dalam memediasi (parcel mediation) pengaruh simpanan terhadap return on aset. Namun jika dilihat dari nilai VAF, variabel kredit mempunyai tingkat mediasi yang lebih baik dibandingkan dengan simpanan, sehingga bagi bank persero untuk meningkatkan return on aset akan lebih mudah jika menyalurkan simpanan dalam bentuk kredit.   Kata Kunci: Harga Emas; Bank; SEM; ROA; Kredit.